FORMATION OF PROFESSIONAL ABILITIES OF FUTURE SKILLED WORKERS FOR AGRICULTURE BY MEANS OF PEDAGOGICAL GAME - Кошук, Олександр (Professional Pedagogics, 2013)
The article reveals topicality concerning elaboration of methodology for formation and development of future workers’ professional abilities by means of pedagogical games because just these individual psychological virtues of a person enable to efficiently manage technical objects, implement their repair and maintenance. The aforementioned task is aimed at advance of future skilled workers’ creative abilities making it an urgent research problem.The essence of concept «pedagogical game», «gaming projection» is analyzed. Major requirements to organizing the imitation-and-game lessons are determined. Methodology for preparing and conducting the seminars on gaming projection as means of involving the students in imitated conditions of engineering performance and hence productive advance of their professional abilitiesiscreated.The author proves purpose and structure of a pedagogical game «Agriculture machine manufacturing» and singles out main stages of its realization. Principle tasks for developing the project while conducting the pedagogical game «Agriculture machine manufacturing» after learning seeding machines are determined.
Keywords: professional skills; educational game; game design; game activity